Identification of chlamydiae and mycoplasma species in ruminants with ocular infections. (1st February 2015) - Gupta, S.; Chahota, R.; Bhardwaj, B.; Priyanka, P.; Verma, S.; Sharma, M.
Abstract: Infectious keratoconjunctivitis (IKC) is a highly contagious ocular inflammatory condition, which is often reported in domestic small and large ruminants. Multiple infectious aetiologies are reported to be involved, but information about the role of certain fastidious bacterial pathogens such as chlamydiae and mycoplasmas is limited in India. Hence, this study was performed to determine the role of these pathogens and their identification by molecular approach. A total of 53 samples from 31 ovine, 14 caprine and eight bovine having clinical symptoms were collected and tested using species‐specific PCR tests for chlamydiae and mycoplasmas followed by nucleotide sequence analysis. The results showed 77·41, 14·29 and 25% samples were chlamydiae positive in ovine, caprine and bovine, respectively, whereas 41·93, 14·29 and 37·5% prevalence of mycoplasma infection was detected in ovine, caprine and bovines, respectively. Chlamydophila abortus, Chlamydophila psittaci, Mycoplasma arginini and Mycoplasma hyorhinis were detected from tested samples. To the best of our knowledge, this is the first time these species are identified in IKC cases from India. Coinfection of both chlamydial and mycoplasmal species was detected in eight IKC cases of ovine which suggest synergistic roles played by both chlamydiae and mycoplasma in IKC samples. Significance and Impact of the Study: Infectious keratoconjunctivitis (IKC) in ruminants has multiple aetiologies, but the role of fastidious chlamydial and mycoplasmal species in clinical cases remains largely unknown. We screened a total of 53 cases of IKC from 31 ovine, 14 caprine and eight bovine, and Chlamydophila abortus, C. psittaci, Mycoplasma arginini and Mycoplasma hyorhinis were detected. These are rarely reported bacteria in clinical IKC. The detection of mixed infection in few cases is also indicative of interspecies synergism. This study highlights the role of lesser reported ocular pathogens in the precipitation of clinical IKC among ruminants that may contribute to a better understanding of pathogenesis and the treatment of IKC.